Thermal management of high-power LED based on thermoelectric cooler and nanofluid-cooled microchannel heat sink. (25th May 2020) - Lin, Xiaohui; Mo, Songping; Mo, Bingzhong; Jia, Lisi; Chen, Ying; Cheng, Zhengdong
Highlights: Nanofluid-cooled microchannel heat sink and thermoelectric cooler are integrated. Cooling performance is tested under wide range of temperature conditions. The proposed system shows good cooling performance for high-power LED. The proposed system shows good cooling performance at high ambient temperature. Using nanofluids instead of water as coolant improves thermal management. Abstract: Effective thermal management for light-emitting diodes (LEDs) is critical, as temperature significantly affects their lifetime and performance. In this study, a system combining a thermoelectric cooler (TEC) and a microchannel heat sink (MHS) is investigated experimentally for thermal management of high-power LEDs. Nanofluids and water are used as coolant. The LED substrate temperature ( T s ) is measured at various TEC powers, nanofluid concentrations, ambient temperatures of LED ( T a ), and ambient temperatures of the fluid radiator ( T a, f ). The effective thermal resistance ( R s-fa ) of the LED substrate to the ambient of the fluid radiator is analyzed. Correlations of T s and R s-fa are obtained. Results show that the T s is lowest when the TEC works at its rated power, and T s is lower than T a at T a ≥ 55 °C. Using nanofluids instead of water as coolant reduces the T s by up to 18.5 °C and decreases the thermal resistance by as much as 42.4%. The MHS heat transfer capacity is increased by 38.6%. The T a, f exhibites greater influence on T s compared to T a . Results show that favorable performance of the thermal management of the high-power LED is obtained by the proposed nanofluid-cooled TEC-MHS system, particularly at high ambient temperature of LED.